Restoring Disturbed Landscapes Putting Principles into Practice - Tongway, David J.; Ludwig, John A.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2011)
Restoring Disturbed Landscapes is a hands-on guide for individuals and groups seeking to improve the functional capacity of landscapes. The book presents a five-step, adaptive procedure for restoring landscapes that is supported by proven principles and concepts of ecological science. Written by restoration experts with a wealth of experience teaching restoration principles and techniques to practitioners and would-be practitioners from a variety of backgrounds, the book offers: an outline of a science-based, ecologically sound approach to restoration discussion of the conceptual framework and rigorous principles that underlie the approach case studies of two types of restoration projects (restoring mined landscapes and restoring damaged rangelands) that illustrate how the approach, framework, and four key principles for restoring landscapes have been implemented a variety of scenarios that represent typical restoration problems and how those problems can be handled indicators for monitoring and how landscape function can be tracked and analyzed as part of a comprehensive monitoring program. Abundantly illustrated with photos and figures that clearly explain concepts outlined in the book, Restoring Disturbed Landscapes is an engaging and accessible work designed specifically for restoration practitioners with limited training or experience in the field. It tells restorationists where to start, what information they need to acquire, and how to apply this information to their specific situations.
Foreword -- Preface -- Acknowledgments -- PART I: A Function-Based Approach to Restoring Disturbed Landscapes. 1. Our Approach to Restoring Disturbed Landscapes: Five-Step Adaptive Procedure -- 2. A Framework for How Landscapes Function -- 3. Principles for Restoring Landscape Functionality -- PART II: Case Studies on Restoring Landscapes: Mine Sites and Rangelands. 4. Restoring Mined Landscapes -- 5. Restoring Damaged Rangelands -- PART III: Scenarios for Restoring Landscapes: Mine Sites, Rangelands, Farmlands, and Roadsides. 6. Restoration of Mine-Site Waste-Rock Dumps -- 7. Restoration of Mine-Site Tailings Storage Facilities -- 8. Restoring Landscapes after Open-Cut Coal Mining -- 9. Restoring Rangelands with an Overabundance of Shrubs -- 10. Renewing Pastureland Functions Using Tree Belts -- 11. Restoration of Former Farmlands near Urban Developments -- 12. Restoring Verges after Road Construction -- PART IV: Monitoring Indicators. 13. Landscape Function Analysis: An Overview and Landscape Organization Indicators -- 14. Landscape Function Analysis: Soil-Surface Indicators -- 15. Ephemeral Drainage-Line Assessments: Indicators of Stability -- 16. Vegetation Assessments: Structure and Habitat Complexity Indicators -- 17. Reflections on Restoring Landscapes: A Function-Based Adaptive Approach -- References -- Glossary -- Further reading -- About the authors -- Index.
Keywords: Environmental sciences; Endangered ecosystems; Landscape ecology; Conservation biology; Environmental management; Nature Conservation; Environment; Environmental Management; Landscape Ecology; Ecosystems; Conservation Biology/Ecology.; Nature Conservation